The Professionalism of Indonesian Teachers in The Future - Iis Lisnawati (STKIP Singkawang, 2018)
Teachers are the most crucial factor in learning. Therefore, the process and success of learning as a determinant of the quality of education in the future were determined by the professionalism of teachers. The professionalism of Indonesian teachers in the future must be in line with the demands of their profession, namely (1) having teacher competence covering pedagogic competence, personality competence, social competence, and professional competence, (2) realizing Indonesian language learning in accordance with current curriculum , (3) implementing the paradigm of 21st century learning that has nationalism, global perspective, and multi-literacy to produce graduates who have soft skill and hard skills that are superior and competitive so that they become qualified human resources.